A New Method To Determine In Vivo Interactomes Reveals Binding of the Legionella pneumophila Effector PieE to Multiple Rab GTPases - Aurélie Mousnier (American Society for Microbiology, 2014)
ABSTRACT Legionella pneumophila, the causative agent of Legionnaires’ disease, uses the Dot/Icm type IV secretion system (T4SS) to translocate more than 300 effectors into host cells, where they subvert host cell signaling. The function and host cell targets of most effectors remain unknown. PieE is a 69-kDa Dot/Icm effector containing three coiled-coil (CC) regions and 2 transmembrane (TM) helices followed by a fourth CC region. Here, we report that PieE dimerized by an interaction between CC3 and CC4. We found that ectopically expressed PieE localized to the endoplasmic reticulum (ER) and induced the formation of organized smooth ER, while following infection PieE localized to the Legionella-containing vacuole (LCV). To identify the physiological targets of PieE during infection, we established a new purification method for which we created an A549 cell line stably expressing the Escherichia coli biotin ligase BirA and infected the cells with L. pneumophila expressing PieE fused to a BirA-specific biotinylation site and a hexahistidine tag. Following tandem Ni2+ nitrilotriacetic acid (NTA) and streptavidin affinity chromatography, the effector-target complexes were analyzed by mass spectrometry. This revealed interactions of PieE with multiple host cell proteins, including the Rab GTPases 1a, 1b, 2a, 5c, 6a, 7, and 10. Binding of the Rab GTPases, which was validated by yeast two-hybrid binding assays, was mediated by the PieE CC1 and CC2. In summary, using a novel, highly specific strategy to purify effector complexes from infected cells, which is widely applicable to other pathogens, we identified PieE as a multidomain LCV protein with promiscuous Rab GTPase-binding capacity. IMPORTANCE The respiratory pathogen Legionella pneumophila uses the Dot/Icm type IV secretion system to translocate more than 300 effector proteins into host cells. The function of most effectors in infection remains unknown. One of the bottlenecks for their characterization is the identification of target proteins. Frequently used in vitro approaches are not applicable to all effectors and suffer from high rates of false positives or missed interactions, as they are not performed in the context of an infection. Here, we determine key functional domains of the effector PieE and describe a new method to identify host cell targets under physiological infection conditions. Our approach, which is applicable to other pathogens, uncovered the interaction of PieE with several proteins involved in membrane trafficking, in particular Rab GTPases, revealing new details of the Legionella infection strategy and demonstrating the potential of this method to greatly advance our understanding of the molecular basis of infection.